Dual-energy CT perfusion imaging for differentiating invasive thymomas, thymic carcinomas, and lymphomas in adults. Issue 6 (June 2022) - Yu, C.H.; Zhang, R.P.; Yang, X.T.; Yang, Z.; Xin, L.; Zhao, Z.Z.; Wang, J.; Wang, L.X.
Abstract : AIM: To evaluate the role of dual-energy computed tomography perfusion (DECTP) imaging in differentiating invasive thymomas (ITs), thymic cancers (TCs), and lymphomas in adults. MATERIALS AND METHODS: Ninety-five patients with solid masses in the prevascular mediastinum who underwent DECTP examinations were enrolled in this study. The perfusion parameters (blood flow, BF; blood volume, BV; mean transit time, MTT; permeability surface, PS) and spectral parameters (water concentration, WC; iodine concentration, IC; normalised iodine concentration, NIC; the slope of spectral radiodensity [Hounsfield units] curve, λHU ) of the lesions were analysed. RESULTS: There were no differences in the MTT or WC values among ITs, TCs, and lymphomas (all p> 0.05). The IC, NIC, and λHU values in the optimal arterial and venous phases and PS values of TCs were higher than those of ITs and lymphomas (all p< 0.05), and there were no differences between ITs and lymphomas (all p> 0.05). The BF and BV values of lymphomas were lower than those of ITs and TCs (all p< 0.05), and there were no differences between ITs and TCs (all p> 0.05). The cut-off values for BF and BV used to differentiate lymphomas from ITs and TCs were 42.83 ml/min/100 g and 4.66 ml/100 g, respectively (area under the receiver operating characteristic curve: 0.847 and 0.839; sensitivity, 80.6% and 82.1%; specificity, 75% and 71.4%; accuracy, 78.9% and 81.1%). CONCLUSIONS: The perfusion and spectral parameters of DECTP imaging help to identify ITs, TCs, and lymphomas, and BF and BV values help to differentiate lymphomas from ITs and TCs. Highlights: Conventional CT features help to distinguish lymphoma from thymic epithelial tumor. Although conventional CT findings are useful, they are prone to subjectivity. BF and BV values could distinguish lymphoma from thymic epithelial tumor.